Partial Sums for a Certain Subclass of Meromorphic Univalent Functions - Aouf, M. K.; Mostafa, A. O.; Lashin, A. Y.; Munassar, B. M. (Sarajevo Journal of Mathematics, 2024)
In this paper, the class $Σ_{λ}\left( α,β,γ\right)$ of univalent meromorphic functions defined using the Ruscheweyh derivative in the punctured unit disk U$^{*}$ is introduced. We study some results concerning the partial sums of meromorphic univalent starlike functions and meromorphic univalent convex functions. 2010 Mathematics Subject Classification. 30C45.